2018
DOI: 10.3390/w10101424
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Morphodynamic Changes of a Tidal River Confluence through Field Measurements and Numerical Modeling

Abstract: A confluence is a natural component in river and channel networks. This study deals, through field and numerical studies, with alluvial behaviors of a confluence affected by both river run-off and strong tides. Field measurements were conducted along the rivers including the confluence. Field data show that the changes in flow velocity and sediment concentration are not always in phase with each other. The concentration shows a general trend of decrease from the river mouth to the confluence. For a given locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In contrast, most 3D numerical models (e.g., Delft3D, Fluent, RSim-3D, SSIIM) solving the fully three-dimensional Reynolds-equations with different turbulence closures, typically permit the application of the equivalent sand roughness k s [51], which is based on the sediment size and also allows accounting for the average height of bed forms. To date, numerous studies [52][53][54][55][56][57][58][59][60][61] have been published based on the mentioned numerical models to calculate hydrodynamic properties and their impacts on rivers.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most 3D numerical models (e.g., Delft3D, Fluent, RSim-3D, SSIIM) solving the fully three-dimensional Reynolds-equations with different turbulence closures, typically permit the application of the equivalent sand roughness k s [51], which is based on the sediment size and also allows accounting for the average height of bed forms. To date, numerous studies [52][53][54][55][56][57][58][59][60][61] have been published based on the mentioned numerical models to calculate hydrodynamic properties and their impacts on rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Bolla Pittaluga et al [13] worked on the morphological equilibrium of many tidal configurations using a 1D model. Xie, et al [14] examined the morpho-dynamics of a tidal confluence through field investigations and numerical simulations. Zhou, et al [15] reviewed the concept of equilibrium and suggested that it can only be found in ideal situations of numerical or physical models.…”
Section: Items Non-tidal Confluence Tide-driven Confluencementioning
confidence: 99%
“…recently published results such as Xie, Yang, Lundström, and Dai (2018) and Xie, Yang, and Lundström (2019).…”
Section: Mathematical Formulationmentioning
confidence: 99%